Two tetranuclear Cu2Ln2 (Ln = Dy, Tb) heterometallic complexes: Structure, solution behavior, and magnetic properties. (21st December 2021) - Yu, Shui; Zhang, Qin‐Hua; Zhu, Jingru; Wei, Fengli; Liu, Dongcheng; Hu, Huancheng; Zou, Hua‐Hong; Liang, Yuning; Liang, Fupei; Chen, Zilu
Abstract: Two tetranuclear 3d–4f heterometallic complexes [Cu2 Ln2 (NO3 )4 (OAc)2 L4 ] (Ln = Dy 1, Tb 2 ) were obtained under solvothermal reactions of 1‐amino‐propan‐2‐ol (HL) with [Cu2 (OAc)4 (H2 O)2 ] and Ln (NO3 )3 ·5H2 O. The structural analyses confirmed a centrosymmetric Z‐shaped skeleton for them with the peripheral positions occupied by two Cu (II) ions. The neighboring two lanthanide ions, as well as the neighboring ions of Ln (III) and Cu (II), are all double‐bridged through two O atoms. The detailed dynamic magnetic investigation showed slow magnetic relaxation behaviors for both complexes with an energy barrier of 1.35(2) and 2.02(4) K for 1 and 2, respectively. Furthermore, it revealed from the electrospray mass spectrometry (ESI‐MS) that complexes 1 and 2 easily undergo dimerization in solution. Abstract : Two novel heterometallic tetranuclear Cu2 M2 (M = Dy, Tb) complexes with similar structures have been prepared, and both of them show slow magnetic relaxation behaviors. High‐resolution electrospray ionization‐mass spectrometry (HRESI‐MS) analysis shows that the complexes polymerized when they are solution state.